Intracellular accommodation of bacteria, fungi, and oomycetes by plants analyzed using transmission electron microscopy - Gantner, Isabella; Gutjahr, Caroline; Ried-Lasi, Martina K.; Cheradil, Andrea; Buchner, Julia; Parniske, Martin; Klingl, Andreas (PLOS Pathogens, 2025)
Transmission electron microscopy was the key for revealing structural similarities between intracellular plant-microbe interactions.